NSTP CWTS 2 : a textbook for the new general education curriculum - Dela Cruz, Sonia Gasilla; Dela Cruz, Edeliza; Mapue, Paul; Lazo, Keith Edzel; Dela Cruz, Kassandraq Gaverielle (Mandaluyong City : Books Atbp. Publishing Corp., 2022)
Anent to the provisions of the Minimum Standards for the National Training Program for Common and Specific Modules of the Commission on Higher Education.
A. Self-Awareness and Values Development -- B. Leadership Training -- C. Dimension of Development -- D. Community Exposure Agency Visits -- E. Community Needs Assistances -- F. Community Service -- G. Program Evaluation.
Includes bibliographical references.
Keywords: SERVICE TRAINING -- PHILIPPINES; MILITARY EDUCATION -- PHILIPPINES